2020
DOI: 10.1007/s11606-020-05802-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing VA and Community-Based Care: Trends in Sleep Studies Following the Veterans Choice Act

Abstract: BACKGROUND:To address concerns about access to care, the Veterans Access, Choice, and Accountability Act of 2014 was enacted to make care available in the community when Veterans Health Administration (VA) care was unavailable or not timely. This paper examined VA referrals for diagnostic sleep studies from federal fiscal year (FY) 2015-2018. DESIGN: Sleep studies completed between FY2015 and 2018 for Veterans tested within VA facilities (VAF) or referred to VA community care (VACC) providers were identified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 28 publications
(35 reference statements)
2
18
0
Order By: Relevance
“…Among patients who did access community care for testing, lack of follow up and poor continuity of care was an important factor influencing preference for VA, previously identified as a factor influencing satisfaction with outsourced care among both patients and providers [ 32 , 33 ]. Our findings further reinforce the need to improve coordination between VA and the community to mitigate potential satisfaction and patient safety issues [ 3 , 32 ].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Among patients who did access community care for testing, lack of follow up and poor continuity of care was an important factor influencing preference for VA, previously identified as a factor influencing satisfaction with outsourced care among both patients and providers [ 32 , 33 ]. Our findings further reinforce the need to improve coordination between VA and the community to mitigate potential satisfaction and patient safety issues [ 3 , 32 ].…”
Section: Discussionsupporting
confidence: 73%
“…In this qualitative evaluation of Veteran experience with the national VA TeleSleep program, Veterans reported high levels of satisfaction across multiple domains. Since implementation in 2017, the TeleSleep initiative has facilitated an increase in the number of Veterans diagnosed with OSA and in the number of encounters for sleep related disorders [ 3 ]. This study provides insight into Veterans’ experiences with TeleSleep and identifies factors affecting participation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analyses showed that in-person testing studies were much more likely for VCP referrals, for persons living in rural areas, those with higher comorbidity scores, and for older Veterans (age 44 and over) compared with younger Veterans. 15 During the Partnership Forum, we shared our current work in progress. This work suggests that Veterans’ care coordination needs will likely differ for those seeking primary care than those seeking specialty services in the community due to different risk profiles and social determinants.…”
Section: Research Prioritiesmentioning
confidence: 99%